2022
DOI: 10.1021/acs.jpclett.1c04242
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Polymer Heterojunction in Colloidal-Phase Plasmonic Catalysis

Abstract: Plasmonic catalysis in the colloidal phase requires robust surface ligands that prevent particles from aggregation in adverse chemical environments and allow carrier flow from reagents to nanoparticles. This work describes the use of a water-soluble conjugated polymer comprising a thiophene moiety as a surface ligand for gold nanoparticles to create a hybrid system that, under the action of visible light, drives the conversion of the biorelevant NAD + to its highly energetic reduced form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[−] AuNRs were used as the sole photocatalyst in the presence of the [Cp*Rh­(bpy)­(H 2 O)] 2+ electron mediator, with triethanolamine (TEOA) as the hole scavenger, under continuous irradiation with a 450 nm CW diode laser for 12 h (light intensity measured at the test tube wall was ∼700 mW cm –2 , Figures a and S4). The photocatalytic conversion of NAD + to NADH by [−] AuNRs was monitored through UV–vis spectroscopy by following the absorption of NADH at ∼340 nm. , All photocatalytic experiments were performed by drop-casting [−] AuNRs on a paper substrate (see Section S1 in the Supporting Information for details) since the [−] AuNRs were losing their colloidal stability during the irradiation under our reaction conditions (Figure S5). The [−] AuNR-loaded paper substrate was characterized with UV–vis–NIR diffuse reflectance spectroscopy, where the presence of both transverse and longitudinal LSPR bands was observed (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[−] AuNRs were used as the sole photocatalyst in the presence of the [Cp*Rh­(bpy)­(H 2 O)] 2+ electron mediator, with triethanolamine (TEOA) as the hole scavenger, under continuous irradiation with a 450 nm CW diode laser for 12 h (light intensity measured at the test tube wall was ∼700 mW cm –2 , Figures a and S4). The photocatalytic conversion of NAD + to NADH by [−] AuNRs was monitored through UV–vis spectroscopy by following the absorption of NADH at ∼340 nm. , All photocatalytic experiments were performed by drop-casting [−] AuNRs on a paper substrate (see Section S1 in the Supporting Information for details) since the [−] AuNRs were losing their colloidal stability during the irradiation under our reaction conditions (Figure S5). The [−] AuNR-loaded paper substrate was characterized with UV–vis–NIR diffuse reflectance spectroscopy, where the presence of both transverse and longitudinal LSPR bands was observed (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The yield of the photoregenerated NADH was estimated to be ∼38% (details on the yield calculation are provided in Section S2 of the Supporting Information). It is worth mentioning that a poor to low yield is often reported in the literature during the plasmonically driven photoregeneration of NADH cofactors by gold nanomaterials ,,, because of the poor charge separation and utilization steps. One of the main reasons for the decent yield obtained in the present study can be attributed to the favorable electrostatic interaction between the [−] AuNRs and [+] [Cp*Rh­(bpy)­(H 2 O)] 2+ , leading to the channeling and increase in the local concentration of the electron mediators close to the surface of the catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, imaging surface molecules remains difficult because of their lack of contrast and sensitivity to the electron beam. Advanced TEM techniques, such as exit wave reconstruction, allow the visualization of hard-soft matter interfaces, for example metal-polymer heterojunctions 225 . This technique may also be applied for 3D characterization, for example, to allow direct visualization of shape-directing additives at the surface of metal nanoparticles.…”
Section: Tomographic and Crystallographic Analysismentioning
confidence: 99%
“…The latter can then lead to the oxidation of another molecule of TEOA, thereby increasing GA production. In recent scientific papers, Grzelczak et al demonstrated the ability of GA to directly reduce NAD + to NADH, thus emphasizing how the TEOA is not an innocent SED but a real player in NAD + reduction; , besides, in one of these papers, they showed also the possibility to decouple in space and time TEOA oxidation and NADH regeneration . This approach enables the NADH regeneration to occur in the absence of light, thereby reducing its degradation due to parasitic photoinduced processes …”
Section: Introductionmentioning
confidence: 99%